A Modified Duodenal Neuroendocrine Tumor Staging Schema Better Defines the Risk of Lymph Node Metastasis and Disease-free Survival. Issue 8 (August 2014) - Kachare, Swapnil D.; Liner, Kendall R.; Vohra, Nasreen A.; Zervos, Emmanuel E.; Fitzgerald, Timothy L.
Duodenal neuroendocrine tumors are rare but increasing in incidence and optimal management is hindered by lack of duodenum-specific staging. Duodenal carcinoids were identified in the Surveillance, Epidemiology and End Results tumor registry. Depth of invasion was defined as limited to lamina propria (LP), invading muscularis propria (MP), through muscularis propria (TMP), and through serosa (S). Nine hundred forty-nine patients were identified with majorities being male (57%), white (70%), and node-negative (87%). Tumor size (cm) was less than 1, 47 per cent; 1 to 2, 35 per cent; and greater than 2, 8 per cent with 76 per cent LP. Lymph node (LN) involvement was associated with age, depth of invasion (LP 4%, MP 28%, TMP 54%, and S 57%) and size (less than 1 cm, 3%; 1 to 2 cm, 13%; and greater than 2 cm, 40%). Using the current T staging, LN involvement was: T1 (LP) 2 per cent, T2 (MP or greater than 1 cm) 13 per cent, T3 (TMP) 54 per cent, and T4 (S) 57 per cent. We reclassified current T1 to T1a and current T2 stage to T1b (1 to 2 cm and LP) and T2 (MP or greater than 2 cm). LN metastasis for T1b tumors was 4.7 per cent compared with 20.8 per cent for T2. The resulting TNM classification better defines 5-year disease-specific survival. Our modified staging schema identifies a low-risk group (T1a and T1b) that may be considered for local therapy.